The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4317/jced.52253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bond strength of orthodontic brackets without enamel etching

Abstract: Background To compare the shear bond strength of brackets with and without enamel etching. Material and Methods In this study, 60 sound premolars were randomly divided into four different groups: 1- TXE group: Enamel etching+Transbond XT adhesive+ Transbond XT composite. 2- TXS group: Transbond plus self-etch adhesive+ Transbond XT composite. 3- PQ1E group: Enamel etching+ PQ1 adhesive+ Transbond XT composite. 4- PQ1 group: PQ1 adhesive+ Transbond XT composite. The shear bond strengths of brackets were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
7
1
1
Order By: Relevance
“…Due to higher shear bond strength in anchor-pylon base brackets and more destructive bond failure mode in this group, greater increase in enamel crack numbers after debonding was anticipated. 28 , 29 Contrary to our prediction, the results demonstrated that enamel crack numbers increased to a greater degree in the anchor-pylon group but this increase was not statistically significant. This might be attributed to the existence of primary cracks before bonding that can serve as stress accumulation regions and may influence developing of new cracks as a confounding factor in both groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Due to higher shear bond strength in anchor-pylon base brackets and more destructive bond failure mode in this group, greater increase in enamel crack numbers after debonding was anticipated. 28 , 29 Contrary to our prediction, the results demonstrated that enamel crack numbers increased to a greater degree in the anchor-pylon group but this increase was not statistically significant. This might be attributed to the existence of primary cracks before bonding that can serve as stress accumulation regions and may influence developing of new cracks as a confounding factor in both groups.…”
Section: Discussioncontrasting
confidence: 99%
“…These factors could influence enamel surface stress reception and damage, which partly confirms longer enamel cracks in the anchor-pylon base bracket group afterdebonding. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…The nanofiller in SBU and the formed thick adhesive layer might induce a beneficial effect in terms of bond strength, via stress relief and cessation of crack propagation, respectively 16 . This positive effect has been demonstrated for filled adhesives in bracket bonding 23 . Less but adequate SBS of self-etch adhesives compared with conventional etching has previously been reported 1 …”
Section: Discussionmentioning
confidence: 91%
“…To calculate the sample size, the software G * Power 3.0.10 (Franz Faul, Universität Kiel, Germany) was used. Based on a similar study [14], an α error � 0.05 and test power of 80% were considered so that 26 specimens per group would be required to detect possible differences, totaling 130 specimens. Bovine incisors [15] free of enamel defects were stored for 1 month in a 0.1% thymol solution to control bacterial growth [16].…”
Section: Sample Calculationmentioning
confidence: 99%